Histological Effect of Aspirin on the Stomach of Male Albino Swiss Mice (Mus musculus) - Al-Timimi, Zainab Karim (Iraqi Journal of Science, 2020)
The present study aimed to determine the impacts of Aspirin drug on the stomach of albino Swiss mice. The study sample included 10 male mice divided into 2 groups. The first group was orally administered with 0.1 mL of 0.75 mg/kg aspirin once daily, whereas the second group, the control, was treated with similar doses of distilled water. Following 60 days of successive treatment, a number of parameters was studied including difference in body weight and histopathological changes in the stomach as diagnosed after histological preparation. The results showed a significant decrease (p<0.05) in body weight average of the treated mice compared with the control group. The results also revealed the occurrence of several histopathological changes in the stomach of treated animals, including raptures in the epithelium lining, congestion in the muscular layer, and vasodilation. In addition, alterations such as hemorrhage, pyknosis in muscle cells, sloughing of the lining of the muscular layer, and external bleeding were observed. It can be concluded from these results that orally administered aspirin exerts negative effects on the stomach in mice.